Óxido de Zinco de altas pressões obtido por moagem mecânica - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The motivation for this research was the synthesis and production of nanostructured materials ZnO (oxide of zinc) starting from Zn (pure zinc) using the high-energy mechanochemical technique (mechanochemistry or mechanochemical), applying the glycerin (C3H8O3) and the stearic acid (C18H36O2) as controlling agents of the process (PCA’s), both considered materials of interest in green chemistry. Through the measuring of X-Ray Diffraction (DRX) allied to the Rietveld Method it was possible to observe and to analyze in function of the times of grinding (0 min, 225 min, 525 min, 825 min, 855 min, 885 min, 915 min, 945 min, 975 min and 1005 min) the structural evolution of the sample. After 525 min a single phase of ZnO was synthesized, with a hexagonal structure of wurtzite type (or B4 type) with an average size of nanometric crystallites. It was also observed that the mechanochemical process does not modify the solubility of Zn according to the equilibrium diagram phase of the material. With the increase of milling time it was observed a polymorphic transition from the hexagonal structure of wurtzite type for a cubic rocksalt structure type (type B1 and type NaCl). The kinetics of the transition was measured by linewidth analysis and variation of the crystallographic parameters obtained in this study.
Keywords: Nanomateriais; Nanopartículas; Moagem mecânica; Difração de raios - X; Método Rietvel d; ZnO; Nanomaterials; Nanoparticles; Mechanical alloying; Diffraction X - ray; Rietveld method; ZnO; ENGENHARIAS: ENGENHARIA DE MATERIAIS E METALURGICA